A case of dermoid: Cyst within a cyst - Ali, Syed Mahbub; Faruq, Mohammad Omar; Ahsan, Syed Sakibul; Shamarukh, Karishma; Sultana, Amina (Bangladesh Critical Care Journal, 2020)
Abstract Not Available Bangladesh Crit Care J September 2020; 8(2): 134-135